Copper and cobalt doped bioactive glass-fish dermal collagen electrospun mat triggers key events of diabetic wound healing in full-thickness skin defect model. (October 2022) - Jana, Sonali; Datta, Pradyot; Das, Himanka; Jaiswal, Satish; Ghosh, Prabal Ranjan; Lahiri, Debrupa; Kundu, Biswanath; Nandi, Samit Kumar
Abstract: The wounds arising out of underlying hyperglycemic conditions such as diabetic foot ulcers demand a multifunctional tissue regeneration approach owing to several deficiencies in the healing mechanisms. Herein, four different types of electrospun microfibers by combining Rohu fish skin-derived collagen (Fcol) with a bioactive glass (BAG)/ion-doped bioactive glass, namely, Fcol/BAG, Fcol/CuBAG, Fcol/CoBAG, and Fcol/CuCoBAG was developed to accelerate wound healing through stimulation of key events such as angiogenesis and ECM re-construction under diabetic conditions. SEM analysis shows the porous and microfibrous architecture, while the EDX mapping provides evidence of the incorporation of dopants inside various inorganic-organic composite mats. The viscoelastic properties of the microfibrous mats as measured by a nano-DMA test show a higher damping factor non-uniform tan-delta value. The maximum ultimate tensile strength and toughness are recorded for fish collagen with copper doped bioactive glass microfibers while the least values are demonstrated by microfibers with cobalt dopant. In vitro results demonstrate excellent cell-cell and cell-material interactions when human dermal fibroblasts (HDFs) were cultured over the microfibers for 48 h. When these mats were applied over full-thickness diabetic wounds in the rabbit model, early wound healing is attained with Fcol/CuBAG, Fcol/CoBAG, and Fcol/CuCoBAG microfibers. Notably, these microfibers-treated wounds demonstrate a significantly (p < 0.01) higher density of blood vessels by CD-31 immunostaining than control, Duoderm, and Fcol/BAG treated wounds. Mature collagen deposition and excellent ECM remodeling are also evident in wounds treated with fish collagen/ion-doped bioactive glass microfibers suggesting their positive role in diabetic wound healing. Graphical abstract: Fish collagen with Cu/Co ions –doped bioactive glass electrospun mats showed immense potential in the healing of diabetic wounds. Along with the promising angiogenic ability of the ions doped into bioactive glass, the collagen too demonstrated excellent ECM remodeling ability by regulating and preserving cellular functions under diabetic conditions. Image 1 Highlights: Electrospun microfibers from Rohu fish collagen and Cu/Co ions-doped bioactive glass/ bioactive glass as diabetic dressing. The microfibers are cytocompatible with human dermal fibroblasts in-vitro. Excellent ECM remodeling and angiogenesis was evident in diabetic-wound in-vivo with the ion-doped type microfibers.